The vygotskian project for a scientific psychology: Notes on “the historical meaning of the crisis in psychology” - Da Costa, Eduardo Moura [UNESP]; Martins, João Batista [UNESP] (Colegio Mayor de Nuestra Senora del Rosario, 2018)
The present essay aims to present the unfolding of some of the main formulations on the method of psychology developed by Vygotsky in his manuscript “The historical meaning of the crisis in psychology”, concluded in 1927 and first published in 1982. From the selection and reading of some texts written after the manuscript, we perform a comparative analysis to demonstrate that although the manuscript was not prepared for publication by the author, several of his ideas are contained in the subsequent production. His prognosis for the crisis of psychology comes from the adoption of the materialist conception of reality and from the analytic method of cognition of facts. We present what their materialist view of psychological phenomena consists of, as well as what constitutes an analytical and not descriptive method of these phenomena. We point out that the “ge-netic-experimental method” is the basis for their future research. Finally, we point out that his work must be read historically, that is, many fundamental principles presented in the manuscript were already present in previous research.
El proyecto vigotskiano para una psicología científica: apuntes sobre “el significado histórico de la crisis de la psicología”
O projeto vigotskiano para uma psicologia científica: Anotações sobre “o significado histórico da crise da psicologia”
Keywords: Crisis of psychology; Method of psychology; Vygotsky